A social trap for the climate? Collective action, trust and climate change risk perception in 35 countries. (March 2018) - Smith, E. Keith; Mayer, Adam
Highlights: Analysis of pro-climate behavior and policy support in 35 nations. We test for a "social trap" where lack of trust blunts the effect of perceived risk. At both the individual and national level, risk and trust are important predictors. Inconsistent interaction between trust and risk perception. A "thin social trap" may exist for social trust for policy support, but not behaviors. Abstract: Climate change presents a global problem that requires a collective, coordinated response to reduce the rate of greenhouse gases currently emitted. But, even in the face of these serious growing dangers, behavioral and policy responses have been rather muted. A growing literature has documented cross-national differences in climate change attitudes and related scholarship has analyzed general environmental concern across nations. Yet there are several holes in our knowledge. In this manuscript, we consider the role of trust, risk perceptions and investigate the possibility of a "social trap" (Rothstein, 2005) whereby a lack of trust blunts the effect of risk perceptions on public willingness to engage in behaviors or support policies to address climate change. Using between- and within- random effects models coupled with survey data from 35 countries, we find that, at the individual level, trust and risk perceptions are generally positively associated with ameliorative behavior and policy support. Results for a contextual effect of trust and risk perceptions are more mixed, and we find only slim support for an interactive relationship between trust and risk perceptions.